Introduction - Edmunds, D.; Wollenberg, Eva Karoline; Contreras, A.P.; Liu Dachang; Kelkar, G.; Sarin, M.; Singh, N.M. (Routledge, 2003)
This chapter explains the purpose and methods of the book Local Forest Management. The book uses 12-20 case studies in each China, Philippines and India to understand the impacts of community-based forest management policies of the last two decades. We define impacts in terms of the changes in economic, resource or political space that local people have in forest management. The research seeks to address what the impacts have been, why they occurred and alternative ways in which community-led management is happening.